Solar Desalination for the 21st Century A Review of Modern Technologies and Researches on Desalination Coupled to Renewable Energies - Rizzuti, Lucio; Ettouney, Hisham M.; Cipollina, Andrea; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Water scarcity affects the African, Asian, European and American continents, causing serious problems of social welfare and stability. This book of the NATO Science Series presents the state of the art of Desalination Technologies driven by Renewable Energies, highlighting the results achieved in the research field and presenting the potentialities of such technologies. Following an Advanced Research Workshop held in Tunisia from the 23rd to the 25th of February 2006 and collecting prominent scientists from more than 20 different countries, several contributions were selected from researchers, technicians, and industrial representatives, each focused on several different aspects of the use of renewable energies for desalination. Moreover, several regional overviews illustrate the actual state of RE exploitation in most of the countries interested by water scarcity and abundant availability of solar, wind and other renewable energies.
SOLAR DESALINATION: A CHALLENGE FOR SUSTAINABLE FRESH WATER IN THE 21ST CENTURY -- DEVELOPMENT OF SOLAR DESALINATION SYSTEMS CONCEPTS FOR IRRIGATION IN ARID AREAS CONDITIONS -- TECHNO-ECONOMIC EVALUATION OF A SOLAR POWERED WATER DESALINATION PLANT -- DYNAMIC MODELING TOOLS FOR SOLAR POWERED DESALINATION PROCESSES DURING TRANSIENT OPERATIONS -- A METHODOLOGY TO PREDICT OPERATION OF A SOLAR POWERED DESALINATION UNIT -- OPTIMIZING COUPLING SMALL DESALINATION UNITS TO SOLAR COLLECTORS: A CASE STUDY -- USING A SIMULATION PROGRAM TO OPTIMIZE THE OPERATING CONDITIONS OF A SOLAR DESALINATION PLANT FOR MAXIMUM PRODUCTION -- DE-CENTRAL WATER AND POWER SUPPLY INTEGRATING RENEWABLE ENERGY - TECHNICAL AND ECONOMIC PERFORMANCE PREDICTION -- MOROCCAN POTENTIALITIES OF RENEWABLE ENERGY SOURCES FOR WATER DESALINATION -- SOLAR ENERGY UTILISATION OPPORTUNITIES IN BULGARIA -- SOLAR WATER DESALINATION IN THE ARAL SEA REGION -- STATUS AND PROSPECTS FOR SOLAR DESALINATION IN THE MENA REGION -- THE POTENTIAL OF RENEWABLE ENERGIES IN SICILY FOR WATER DESALINATION APPLICATIONS -- THE PSA EXPERIENCE ON SOLAR DESALINATION: TECHNOLOGY DEVELOPMENT AND RESEARCH ACTIVITIES -- A REVIEW OF DESALINATION BY SOLAR STILL -- SOLAR THERMAL DESALINATION USING THE MULTIPLE EFFECT HUMIDIFICATION (MEH)-METHOD -- BEYOND PILOT PROJECTS: THE FEASIBILITY OF IMMEDIATE TECHNOLOGY TRANSFER FROM TRIED AND TESTED MARITIME AND OFFSHORE REVERSE OSMOSIS SYSTEMS TO STATIONARY SOLAR AND WIND POWERED DESALINATION SOLUTIONS -- SOLAR STILLS: 10 YEARS OF PRACTICAL EXPERIENCE IN COMMERCIALISING SOLAR STILLS WORLDWIDE -- SOLAR DRIVEN DESALINATION SYSTEMS BASED ON MEMBRANE DISTILLATION -- POTENTIAL APPLICATION OF SOLAR HEAT COLLECTORS TO AN EASYMED® THERMAL DESALINATION UNIT -- MEMBRANE DESALINATION DRIVEN BY SOLAR ENERGY -- SMALL AUTONOMOUS RO DESALINATION SYSTEMS POWERED BY RENEWABLE ENERGIES. TECHNOLOGICAL ADVANCES AND ECONOMICS -- DESALINATION WITH WIND AND WAVE POWER -- DESALTED WATER FROM A HYBRID RO/MSF PLANT WITHRDF COMBUSTION: MODELLING AND ECONOMICS -- AUTONOMOUS DESALINATION UNITS BASED ON RENEWABLE ENERGY SYSTEMS - A REVIEW OF REPRESENTATIVE INSTALLATIONS WORLDWIDE -- ASSESSMENT OF MOST PROMISING DEVELOPMENTS IN SOLAR DESALINATION.
Keywords: ENGINEERING; ENGINEERING ECONOMY; ENVIRONMENTAL POLLUTION; ENGINEERING; ENGINEERING ECONOMICS, ORGANIZATION, LOGISTICS, MARKETING; RENEWABLE ENERGY SOURCES; WASTE WATER TECHNOLOGY / WATER POLLUTION CONTROL / WATER MANAGEMENT / AQUATIC POLLUTION